Diagnostic laparotomy in suspected malignant lymphoma. - Barr, L. C. (Royal College of Surgeons of England, 1984)
The place of laparotomy in the initial diagnosis of malignant lymphoma is investigated by reviewing a group of 25 patients with suspected lymphoma referred for diagnostic laparotomy. Intra-abdominal malignancy was found in 11 patients, although only 7 of these had a malignant lymphoma. A positive alternative diagnosis was made in a further 8 of the remaining 14 patients, but 6 patients remained undiagnosed following laparotomy. A scheme for the investigation of patients with suspected malignant lymphoma is therefore proposed. Patients with an abdominal mass other than a palpable liver or spleen should undergo early laparotomy, while those with no abdominal mass should undergo an extensive screening programme, appropriate to the mode of presentation and similar to that used in the investigation of a pyrexia of unknown origin, in which diagnostic laparotomy is used only as the final step.